Miocene Glacial Dynamics Recorded by Variations in Magnetic Properties in the ANDRILL‐2A Drill Core. Issue 3 (25th March 2019) - Jovane, Luigi; Florindo, Fabio; Acton, Gary; Ohneiser, Christian; Sagnotti, Leonardo; Strada, Eleonora; Verosub, Kenneth L.; Wilson, Gary S.; Iacoviello, Francesco; Levy, Richard H.; Passchier, Sandra
Abstract: During the 2007 ANtarctic geological DRILLing (ANDRILL) campaign in the Ross Sea, Antarctica, the AND‐2A core was recovered through a stratigraphic succession spanning 1, 138.54 m of Neogene sedimentary rocks that include an expanded early to middle Miocene sequence. The study reported here focuses on the magnetic properties of the interval from 778.63 m below sea floor (mbsf) to 1, 138.54 mbsf, which comprises a time interval spanning 1.5 Myr, from ~18.7 to ~20.2 Ma. We recognize three main pulses of increased input of magnetic materials to the drill site between 778.34–903.06, 950.55–995.78, and 1, 040–1, 103.96 mbsf. Trends in the magnetic mineral concentration dependent parameters mirror changes in the proportion of sediments derived from McMurdo Volcanic Group rocks. We suggest that these pulses in magnetic mineral concentration reflect changes in sediment transport processes associated with changing glacial conditions at the drill site that included (1) subglacial and grounding zone proximal settings, (2) hemipelagic and neritic conditions with abundant sediment‐rich icebergs, and (3) grounding zone‐distal environment that was covered by land‐fast multiyear sea ice or a fringing ice shelf. The magnetic minerals record preserved in the AND‐2A core supports other data that indicate a highly dynamic and variable coastal environment during the early Miocene, where glaciers retreated inland under warm climatic conditions and advanced beyond the drill site across the continental shelf when cold climate prevailed. Key Points: We investigate Miocene glacial dynamics recorded by variations in magnetic properties in the ANDRILL‐2A drill core Pulses in magnetic mineral concentration reflect changes in sediment transport processes associated with changing glacial conditions We refine previous environmental interpretations and delineate a complex early Miocene paleoenvironment in the southern McMurdo Sound